POLITIK ATAS NAMA ALLAH - Mathias Daven (Institut Filsafat dan Teknologi Kreatif Ledalero, 2019)
Abstract: Islamism has all of the characteristics of other secularideologies, such as the faith that it has and offers the one and onlyabsolute truth and thus claims that it reserves the right to imposelaw which must be obeyed by the society. Its ideological thoughtwhich can endanger peace is that political views are consideredto be truth. On this basis, the society tends to be mapped outaccording to the right/wrong schema and therefore the ownersof truth feel legitimized to disregard and oppress groups whichthey consider wrong. This has a serious consequence for realisticunderstanding of what politics is. One typical, main characteristicof an ideological thought is that obliterating enemies is consideredas an essential part of political duties, which is a principle to watchout for. Politics is not theory but praxis (action) and hence thereis no absoluteness. Consequently, there are always pro and contra,the need for consideration, and the possibility of compromises. Inall political process, there would be the winner and loser, but therewould be no right and wrong. The role of politics lies in an effortto ensure peaceful social life with freedom and justice amongpeople of different religious backgrounds who are determined tobuild a nation together.Keywords: Politics, Islamism, Ideology, Ideological Thought